1983
DOI: 10.2136/sssaj1983.03615995004700030028x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus Application Method and Nitrogen Source on Winter Wheat Grain Yield and Leaf Tissue Phosphorus

Abstract: The positive effect of placing N (especially NH+4‐N) with P on crop growth has been demonstrated many times in short‐term greenhouse studies. Under field conditions, however, the effect has not been well defined. The present objective was to evaluate N and P placement methods on the P nutrition and final grain yield of wheat (Triticum aestivum L.) grown in the field and greenhouse. Anhydrous ammonia (NH3), urea‐ammonium nitrate solution (UAN), and sodium nitrate (SN) were N sources while liquid ammonium polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…This effect has been observed with many NH 4 salts Miller et al 1970;Leikam et al 1983;Sangakkara and Cho 1987;Flaten 1989;Bengtsson et al 1994), and with some non-NH 4 salts Ernani and Barber 1991). The influence is attributed either to chemical effects that alter the dissolution and the mobility of added fertilizer or to physiological effects that change the uptake pattern of P by plants.…”
mentioning
confidence: 73%
“…This effect has been observed with many NH 4 salts Miller et al 1970;Leikam et al 1983;Sangakkara and Cho 1987;Flaten 1989;Bengtsson et al 1994), and with some non-NH 4 salts Ernani and Barber 1991). The influence is attributed either to chemical effects that alter the dissolution and the mobility of added fertilizer or to physiological effects that change the uptake pattern of P by plants.…”
mentioning
confidence: 73%
“…It has been known for some time that co-application of ammonium salts increases the solubility and effectiveness of P fertilisers. This has been attributed to both stimulation of root P uptake and to increases in solubility of the P (Starostka and Hill 1955;Bouldin and Sample 1958;Miller et al 1970;Leikam et al 1983). In glasshouse experiments Miller et al (1970) showed that co-application of ammonium sulfate ((NH 4 ) 2 SO 4 ) with monocalcium phosphate (MCP) increased the recovery of fertiliser by maize, and these authors were able to demonstrate a reduced precipitation of Ca-P compounds at the root surface when ammonium salts were co-located with the MCP, largely as a result of a rhizosphere pH reduction.…”
Section: Fertiliser Formulations To Improve Puementioning
confidence: 99%
“…This was attributed to anion competition between sulphate and phosphate for precipitation reactions with Ca 2' . Previous studies (Leikam et al 1983;Westfall and Hanson 1985;Beever and Racz 1987;Kouboura et al 1995) also showed that it is possible to modify the chemical environment of the soil-P fertilizer reaction zone in order to increase the solubility and transport of the applied P in the soil solution, and consequently its uptake by crops. This was accomplished through mixing of non-phosphate salts with fertilizer P as dual bands.…”
mentioning
confidence: 98%